Populations at high risk of cervical cancer in Guangxi Province: Findings from two screening projects in a minority area of South China. (March 2022) - Lu, Huaxiang; He, Haoyu; Qin, Jian; Chen, Mingjian; Liu, Qiumei; Li, Min; Huang, Yongsheng; Wei, Anxiang; Liu, Shuzhen; Xu, Min; Zhang, Zhiyong
Objective: To analyse the positive rates of low-grade (LSIL) and high-grade (HSIL) squamous intraepithelial lesions, and cervical cancer (CC), and identify groups at high risk for CC in Guangxi. Setting: CC screening options in Guangxi, which is the only minority autonomous area in South China, include the National Cervical Cancer Screening Project (NCCSP) and physical examination (PE). Methods: This study was based on PE and NCCSP sample data obtained from 2012 to 2019. We calculated the positive rates of LSIL, HSIL, and CC; analysed the adjusted odds ratio (aOR) and 95% confidence intervals (CI) of the variables in multivariate logistic regression; and subsequently identified groups at high risk for CC. Results: The positive rates of LSIL, HSIL, and CC for the total of 873, 880 samples were 1.89%, 0.60%, and 0.03%, respectively. Females over 64 years of age (vs. 50–64; aOR = 2.05; 95% CI, 1.71–2.46; P  < 0.001) and those from urban (vs. rural; aOR = 1.66; 95% CI, 1.57–1.76; P  < 0.001), minority (vs. non-minority; aOR = 1.24; 95% CI, 1.13–1.35; P  < 0.001), and coastal (vs. inland; aOR = 1.15; 95% CI, 1.06–1.25; P  = 0.001) areas were associated with a high risk of HSIL. Females over 64 (vs. 50–64; aOR = 4.37; 95% CI, 2.88–6.63; P  < 0.001) and those from urban (vs. rural; aOR = 3.05; 95% CI, 2.36–3.95; P  < 0.001) areas were significantly associated with a high risk of CC. Conclusion: Females from urban areas in Guangxi are at high risk for CC. Public health strategies should focus on high-risk populations.